2020
DOI: 10.1007/jhep07(2020)203
|View full text |Cite
|
Sign up to set email alerts
|

Fermionic pole-skipping in holography

Abstract: We examine thermal Green's functions of fermionic operators in quantum field theories with gravity duals. The calculations are performed on the gravity side using ingoing Eddington-Finkelstein coordinates. We find that at negative imaginary Matsubara frequencies and special values of the wavenumber, there are multiple solutions to the bulk equations of motion that are ingoing at the horizon and thus the boundary Green's function is not uniquely defined. At these points in Fourier space a line of poles and a li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 38 publications
(110 reference statements)
2
47
0
Order By: Relevance
“…This study also allows us to uncover some features of how the poleskipping phenomenon manifests itself when the field theory lives in a curved space. For some other recent studies regarding pole-skipping, see [36][37][38][39][40][41].…”
Section: Jhep09(2020)111mentioning
confidence: 99%
See 2 more Smart Citations
“…This study also allows us to uncover some features of how the poleskipping phenomenon manifests itself when the field theory lives in a curved space. For some other recent studies regarding pole-skipping, see [36][37][38][39][40][41].…”
Section: Jhep09(2020)111mentioning
confidence: 99%
“…As a consequence, the corresponding Green's function becomes ill-defined at this special point. It was later observed that pole-skipping also occurs in other sectors of gravitational perturbations, and also for scalar, vector and fermionic fields, being always related to a special property of the near-horizon equations of motion [30][31][32][33]40]. All these studies considered the case of planar black holes, in which the perturbations can be decomposed in terms of plane waves.…”
Section: Jhep09(2020)111mentioning
confidence: 99%
See 1 more Smart Citation
“…Holographically, it has been studied mainly for the Schwarzschild black hole [22,24] as well as for a neutral black hole that explicitly breaks translation invariance [23]. The fermionic case was considered in [25]. From the field theory perspective, this phenomenon was investigated in [26] for effective field theories and in [27] for conformal field theories with large central charge.…”
Section: Jhep10(2020)121mentioning
confidence: 99%
“…However the resultant pole-skipping points in such cases lie totally in the lower half of Imw − Imq plane. See also[64][65][66][67][68][69][70][71][72][73][74].…”
mentioning
confidence: 99%